EFEKTIVITAS WEBSITE DINAS PARIWISATA DAN KEBUDAYAAN PROVINSI JAWA BARAT SEBAGAI MEDIA INFORMASI BAGI WISATAWAN - Walvin Naibaho; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The Culture and Tourism Departement of West Java Province is one of instace under Indonesia culture ministry that manages the problem of culture in west java province.This reseacrh is done to know the effectivity of website as information media for tourist it’s about the respond of people about the culture and tourism department of west java province the reseacrh uses quantitative descriptive method to discuss about the problem. The sample of this research are 100 respondent that taken by using sampling of incidental and data colletion ofe this research uses observation, interview, questioner, and documentation. The scale of measure uses likert scala as the value of responce the respondent.Keywords: Effectivity, Website, Information media, Internet, West Java Province